A new species of Neorhinotora Lopes, 1934 (Diptera: Heleomyzidae) and new records of the genus from Northeastern Brazil - Reis, Geniana Alves; Tôrres, Alice; Ale-Rocha, Rosaly; Oliveira, Francisco Limeira-De- (Zootaxa, 2023)
The Neotropical genus Neorhinotora Lopes is currently represented by five species: N. amapaensis Guimarães & Papavero, N. aristalis (Fischer), N. diversa (Giglio-Tos), N. elsalvadorensis Menezes, Calhau & Ale-Rocha, and N. mutica (Schiner). A new species is described and illustrated: Neorhinotora fapema, sp. nov. from Maranhão, Brazil, bringing the number of valid species to six. A revised key is provided for species identification.